Gonolobus gonzaleziarum (Apocynaceae), a new species from the Tropical Madrean ecoregion in the Sierra Madre Occidental, Mexico - Pío-León, Juan F.; Castro-Castro, Arturo; Alvarado-Cárdenas, Leonardo O. (Instituto de Ecología, A.C., 2023)
Background and Aims: Gonolobus comprises around 150 species in the world, with just over 40 of them distributed in Mexico. In the last two years, at least five new species have been described for this country. This paper describes a new species within the subgenus Pseudolachnostoma.Methods: Thirteen herbaria, three digital databases, and specialized literature were revised. Based on this, similar species were compared, and an identification key was generated. Field expeditions were made from 2019 to 2022 to gather botanical collections and monitor the phenology of the species of interest. The cohesive species concept was proposed as an explanatory hypothesis for the recognition of the taxa discussed here. Key results: The new species, Gonolobus gonzaleriarum, is described and located in two forests of Pinus-Quercus between the southeastern and southwestern limits of the states of Sinaloa and Durango, respectively. It differs from the species of the subgenus Pseudolachnostoma by having a gynostegium with a reduced stipe, lobes of the corolla and sepals of shorter length than the tube, citrus aroma, and a dense inflorescence. We included photographic plates, and an illustration with the distinctive characters, as well as a dichotomous key for the species of the subgenus Pseudolachnostoma. Based on its reduced range and impacted habitat, it is considered a threatened species, according to IUCN criteria. Conclusions: With the present discovery, the genus Gonolobus reaches 45 species in Mexico with 24 endemics. Gonolobus gonzaleriarum has great ornamental potential considering its conspicuous inflorescences and pleasant citrus aroma, which could encourage strategies for its conservation, since it is found in a restricted distribution and threatened habitat.